2021
DOI: 10.1186/s10194-021-01301-y
|View full text |Cite
|
Sign up to set email alerts
|

Identifying genetic variants for age of migraine onset in a Han Chinese population in Taiwan

Abstract: Background Considering the involvement of genetics in migraine pathogenesis in diverse ethnic populations, genome-wide association studies (GWAS) are being conducted to identify migraine-susceptibility genes. However, limited surveys have focused on the onset age of migraine (AoM) in Asians. Therefore, in this study, we aimed to identify the susceptibility loci of migraine considering the AoM in an Asian population. Methods We conducted a GWAS in 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Studies have suggested that the link between migraine and diabetes may be caused by insulin resistance, which plays a vital role in developing metabolic syndrome and is also a risk factor for migraine [26,107]. A GWAS study conducted in 715 patients with Han Chinese ethnicity in Taiwan discovered that one SNP (rs146094041) in the Oestrogen related receptor gamma gene (ESRRG) was genome-wide significantly associated (p = 3.40 × 10 −9 ) with migraine onset before the age of 12 years (www.ebi.ac.uk/gwas/, accessed on 13 March 2022) [242]. Given the involvement of sex hormones, especially oestrogen, in migraine pathophysiology [107,243], the link between migraine and diabetes may be partially explained by sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that the link between migraine and diabetes may be caused by insulin resistance, which plays a vital role in developing metabolic syndrome and is also a risk factor for migraine [26,107]. A GWAS study conducted in 715 patients with Han Chinese ethnicity in Taiwan discovered that one SNP (rs146094041) in the Oestrogen related receptor gamma gene (ESRRG) was genome-wide significantly associated (p = 3.40 × 10 −9 ) with migraine onset before the age of 12 years (www.ebi.ac.uk/gwas/, accessed on 13 March 2022) [242]. Given the involvement of sex hormones, especially oestrogen, in migraine pathophysiology [107,243], the link between migraine and diabetes may be partially explained by sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Stritt reported that exercise increased serotonin (5-HT) levels, even with low intensity exercise [ 39 ], and 5-HT played an important role in many cognitive processes. Tsai reported that acute exercise-induced neurocognitive changes were associated with real-time changes in circulating levels of neuroprotective growth factors, and acute exercise increased the amplitude of the event-related potential, P3 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that first-degree relatives had an increased risk of migraines with and without aura [37]. In the GWAS study, which included the determination of genes involved in the age of onset and pathology of migraines in Asians, one SNP was associated with 12 years of age and five SNPs were associated with migraines [38]. However, an important limitation of these studies is the patient grouping method, with grouping based on aura and family history.…”
Section: Discussionmentioning
confidence: 99%